2016
DOI: 10.1166/jnn.2016.11988
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of HA Coated Titanium Dioxide Nanotubes

Abstract: CP Grade II titanium was first anodized in order to form TiO2 nanotubes, and then the TiO2 nano- tubes were coated with hydroxyapatite using the sol-gel method. The electrochemical properties of pure Ti, anodized TiO2 nanotubes, and HA-coated TiO2 nanotubes were investigated using poten- tiodynamic polarization and impedance tests. The sol-gel-coated HA nanoparticles were observed to sufficiently penetrate into the TiO2 nanotubes, and the polarization resistance of the HA-coated titanium nanotubes was higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The anodized TiO 2 layer enhances the corrosion resistance by being as a barrier to embed the releasing of metallic ions. This is also confirmed by Kang et al [131] who reported an enhancement in electrochemical properties by lowering in corrosion current density and development in corrosion resistance after anodizing the surface of cp-Ti coated by sol-gel hydroxyapatite.…”
Section: Tio 2 Interlayer Prepared By Anodizationsupporting
confidence: 85%
“…The anodized TiO 2 layer enhances the corrosion resistance by being as a barrier to embed the releasing of metallic ions. This is also confirmed by Kang et al [131] who reported an enhancement in electrochemical properties by lowering in corrosion current density and development in corrosion resistance after anodizing the surface of cp-Ti coated by sol-gel hydroxyapatite.…”
Section: Tio 2 Interlayer Prepared By Anodizationsupporting
confidence: 85%
“…Although, this native TiO2 reduce the corrosion of Ti and have ability to promote biocompatibility, this one can be damaged easily by mechanical stress [37]. Therefore, there is a need to applied proper surface modification of titanium surface because it leads to an increase in its roughness, thereby improving the adhesion of the bioactive ceramic coating to the implanted titanium surface [38]. Most titanium implants are treated with bioactive ceramic material in order to improve biocompatibility, osteointegration and coating adhesion on the substrate [38][39][40].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Taking into account these considerations, there is a requirement for suitable surface modification of titanium and its alloys that will result in improved biocompatibility and osteointegration, with simultaneous reduction of strong bacterial seeding on the implant surface. , Generally, titanium implants are treated with bioactive materials, in most cases, bioactive ceramic materials, in order to improve implant biocompatibility and osteointegration. …”
Section: Introductionmentioning
confidence: 99%